Designation of the Parties to Bills of Exchange which Provide for the Validity of Promissory Notes - Szuma, Krzysztof (Studia Oeconomica Posnaniensia, 2015)
Bills of exchange and promissory notes are the basis of contractual relationships; and as legal securities, the laws relating to them require that the expressions of these relationships are defined in the documents. Since, by definition, securities are characterised by the fact that an obligation cannot be fulfilled without the submission of a document, it has to be highly formalized with regard to its features. Consequently, once issued it is not possible to make any additions or amendments. Also, it cannot be interpreted more broadly or differently than the options indicated in Article 2 and 102 of the law on bills of exchange and promissory notes. Additionally, it is not possible to interpret it based on any other documents, even though these documents are not contested by parties of a promissory note. As is clear from the case law on bills of exchange and promissory notes, only such highly formalized documents meet the requirements for establishing the contractual relationships regarding these securities.